PENGARUH MOTIVASI KERJA TERHADAP KOMITMEN AFEKTIF DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIATOR DI HOTEL X - Harianto, Agung (KINERJA, 2016)
AbstractThis research is quantitative. The analysis technique used in this study is a partial least square (PLS). The results showed that working motivation has a positive and significant impact on Job Satisfaction, and also has a positive and significant impact on Affective Commitment. While job satisfaction has positive effect but not significant to Affective Commitment, Job Satisfaction proven that is not a variable intermediary between Work Motivation and Affective Commitment.Keywords: Work Motivation, Job Satisfaction, Affective Commitment